Sistema de monitoramento de transformadores de distribuição utilizando modelos térmicos e tecnologias Java e Bluetooth - Lima, Sérgio dos Santos (2012)
This paper presents the development and evaluation of a monitoring system with Bluetooth and Java technology to aid managing the condition of distribution transformers through thermal models. It is well known that monitor the condition of transformers has been the subject of concern in relation to avoid economic losses caused by equipment failure. It is possible, through the system management: (i) maximize the life time of the monitored equipment, (ii) improve the reliability of the electrical grid and (iii) reduce its maintenance costs. Through a bibliographical survey of transformer condition monitoring systems and study of thermal models applied to transformers, was developed a system for data acquisition and an interface for data analysis. This work brings a contribution to the development of these systems, proposing the use of mobile devices as a viable strategy to collect data of distribution transformers and using data collected by those devices for generating thermal models (to estimate top-oil and hotspot temperature) that will let us: (i) establish maximum load for the equipment, and (ii) estimate the loss of life. The information provided by the condition monitoring system proposed should serve as support to electric utility company to implement action plans to help possible exchange of equipment, do a more balanced load in their distribution transformers and help prioritizing, in case of any necessary actuation of the system protection